The Role of Skeletal Muscles in Exertional Heat Stroke Pathophysiology - Laitano, Orlando; Oki, Kentaro; Leon, Lisa R. (International Journal of Sports Medicine, 2021)
The active participation of skeletal muscles is a unique characteristic of exertional heat stroke. Nevertheless, the only well-documented link between skeletal muscle activities and exertional heat stroke pathophysiology is the extensive muscle damage (e. g., rhabdomyolysis) and subsequent leakage of intramuscular content into the circulation of exertional heat stroke victims. Here, we will present and discuss rarely explored roles of skeletal muscles in the context of exertional heat stroke pathophysiology and recovery. This includes an overview of heat production that contributes to severe hyperthermia and the synthesis and secretion of bioactive molecules, such as cytokines, chemokines and acute phase proteins. These molecules can alter the overall inflammatory status from pro- to anti-inflammatory, affecting other organ systems and influencing recovery. The activation of innate immunity can determine whether a victim is ready to return to physical activity or experiences a prolonged convalescence. We also provide a brief discussion on whether heat acclimation can shift skeletal muscle secretory phenotype to prevent or aid recovery from exertional heat stroke. We conclude that skeletal muscles should be considered as a key organ system in exertional heat stroke pathophysiology.
Keywords: myopathy; illness; hyperthermia; immune response